Exploring the attitudes of girl learners with physical disabilities towards education in Kisumu, Kenya - Janet Auma Odhiambo (International Journal of Studies in Inclusive Education)
The study explored the attitudes of girl learners with physical disabilities (GLwPDs) toward their education. It adopted a descriptive exploratory design within a qualitative approach. Fifty participants including eighteen GLwPDs, twenty of their parents, ten teachers in a special school for the physically challenged, and two opinion leaders participated. They were selected through convenience and purposive sampling techniques. Data were collected through interviews, focus group discussions and document analysis. The thematic findings revealed that GLwPDs had negative attitudes toward their education. Comparing the girls with physical disabilities to their non-disabled peers, most parents are reluctant to take them to school.